2010
DOI: 10.1074/jbc.m110.166041
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal Region of Twitchin Binds Thick and Thin Contractile Filaments

Abstract: Catch is a mechanical state present in some invertebrate smooth muscles in which force output and high resistance to muscle lengthening are maintained for long periods of time with very low energy utilization. In the catch state, intracellular [Ca 2ϩ ] is close to basal concentration (1), and redevelopment of force following unloading of the muscle is absent (2). A hypothesis to explain the long term maintenance of catch force was based on a slowing of cycling of myosin attached to actin when activation wane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In the tri-helix bundle a highly conserved sequence was found that bears homology to the actin binding sequences of troponin I, twitchin, and other actin binding proteins [8, 11, 23]. Missense variants associated with hypertrophic cardiomyopathy also affected actin binding, further supporting the idea that tri-helix bundle mediates actin binding of the motif [5].…”
Section: Introductionmentioning
confidence: 92%
“…In the tri-helix bundle a highly conserved sequence was found that bears homology to the actin binding sequences of troponin I, twitchin, and other actin binding proteins [8, 11, 23]. Missense variants associated with hypertrophic cardiomyopathy also affected actin binding, further supporting the idea that tri-helix bundle mediates actin binding of the motif [5].…”
Section: Introductionmentioning
confidence: 92%
“…Additionally, twitchin, a protein similar to titin, characterized in C. elegans as a thick filament regulatory protein, interacts with both myosin and actin in a phosphorylation-dependent manner to modulate cross-bridges formation [78, 79]. However, current models (as described above) to explain the mechanism of contractile regulation through dynamic binding to myosin and actin are lacking.…”
Section: The Regulatory Activities Of Mybp-c-models and Perspectivesmentioning
confidence: 99%
“…Once Ca 2+ concentrations decrease to resting levels, catch muscle enters the high-tension catch state, which is able to be maintained for long periods of time. Twitchin, a giant myosin-associated protein, is thought to tether together the thin and thick filaments through its phosphorylation sites [2] [3] [4].…”
Section: Introductionmentioning
confidence: 99%